DETERMINANT FINANCING RISK ON ISLAMIC RURAL BANKS IN INDONESIA: ARDL APPROACH - Rifadli D. Kadir; Chitra Yuliashri Katili (Journal of Management and Islamic Finance, 2021)
This study aims to analyze internal and external factors that affect Financing Risk as proxied by NPF at Islamic People's Financing Banks in Indonesia. By using the Auto Regressive Distributed Lag (ARDL) analysis, it was found that the CPI has a positive and significant effect, the exchange rate does not have a positive effect on the NPF, the Industrial Production Index (IPI) as a proxy for GDP in this study has a positive and significant effect, ROA has no negative effect on the NPF Sharia BPR in Indonesia, Bank Size has a negative and significant effect, CAR has no effect on NPF, FDR has a positive and significant effect, BOPO has a negative and significant effect on NPF as a proxy for Financing Risk at Sharia BPR in Indonesia.